Method for treating organic pollutants by using zeolite-based catalytic adsorption material

By treating Beta zeolite with acid, alkali and template agent to form a multi-stage mesoporous structure and loading Cu, zeolite-based catalytic adsorption material was prepared, which solved the problems of high synthesis cost, high toxicity and low toluene adsorption efficiency of Beta zeolite, and achieved efficient adsorption of toluene and low temperature catalytic oxidation.

CN119500063AInactive Publication Date: 2025-02-25YANGZHOU POLYTECHNIC INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693267.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Beta zeolite molecular sieve has problems such as high cost, high toxicity, and complex post-treatment in synthesis, and has failed to achieve efficient adsorption of toluene.

Method used

By post-treatment of Beta zeolite with acid, alkali, and template agent, a multi-stage mesoporous structure is formed, and the supported active component Cu is impregnated on its surface to prepare a zeolite-based catalytic adsorption material.

Benefits of technology

The specific adsorption capacity of Beta zeolite toluene is improved, and the complete catalytic oxidation and degradation of p-toluene is achieved under low temperature conditions, with low cost and significant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151520180000031
    Figure BDA0005151520180000031
  • Figure BDA0005151520180000032
    Figure BDA0005151520180000032
  • Figure BDA0005151520180000061
    Figure BDA0005151520180000061
Patent Text Reader

Abstract

The invention relates to a method for treating organic pollutants by using a zeolite-based catalytic adsorption material, which comprises the following steps: carrying out post-treatment on the surface of Beta zeolite by using acid, alkali and a template agent to form a multistage mesoporous structure on the surface of the Beta zeolite, and then impregnating and loading Cu, so that the obtained catalytic adsorption material can realize complete catalytic oxidation degradation on toluene under a low-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic oxidation, and relates to a method for treating organic pollutants using a zeolite-based catalytic adsorption material. Background Art

[0002] As people's requirements for environmental protection and attention to air quality increase, PM2.5 emission reduction has become an urgent and challenging issue. x ), volatile organic compounds (VOCs), SO 2 etc. are the main causes and sources of PM2.5, and their efficient elimination is the current focus of attention.

[0003] Toluene is an important chemical raw material, which can be used to make spray paint, explosives, pesticides, benzoic acid, dyes, synthetic resins and polyester, etc. Toluene can also be used as a solvent, and it is also a component of gasoline. This substance has serious harm to the environment and can cause pollution to the air, water environment and water sources, so it needs to be handled with caution.

[0004] Beta zeolite molecular sieve has a good performance in adsorbing organic pollutants, but the current Beta zeolite molecular sieve has problems such as high cost, high toxicity, and complex post-treatment in synthesis, and it has not yet achieved efficient adsorption of toluene. Therefore, it is extremely important to develop a low-cost method for synthesizing Beta zeolite and modify it to further improve the adsorption of toluene. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a method for treating organic pollutants using a zeolite-based catalytic adsorption material. The zeolite-based catalytic adsorption material used is obtained by post-treating the surface of Beta zeolite with acid, alkali, and template agent to form a multi-level mesoporous structure on its surface, thereby increasing its effective active surface area and improving the specific adsorption of toluene. The active component Cu is then impregnated and loaded on its surface to achieve complete catalytic oxidation of the adsorbed toluene.

[0006] The zeolite-based catalytic adsorption material is prepared by subjecting a precursor containing a sodium source, a silicon source and an aluminum source to hydrothermal crystallization treatment in a tetraethylammonium ion aqueous solution to convert the precursor into Beta zeolite. The Beta zeolite is then treated twice with an acid, an alkali and a template agent to form a multi-level mesoporous structure on the surface of the zeolite, and then impregnated with loaded Cu.

[0007] During the synthesis of Beta zeolite, the sodium source Na 2 O is measured in , silicon source is measured in SiO 2 Aluminum source Al 2 O 3 In terms of calculation, Na 2 O:Al 2 O3 :SiO 2 The molar ratio is X:Y:100, wherein X=2-40, Y=0.25-10.

[0008] The silicon source preferably includes at least one of silicon oxide, silica sol and silicate; the aluminum source preferably includes at least one of aluminum oxide, aluminum salt and aluminate. The silicon source and the aluminum source more preferably also include Beta zeolite seed crystals.

[0009] The Beta zeolite seed crystals preferably account for 80% by weight or less of the precursor molded product.

[0010] The tetraethylammonium is preferably derived from at least one of tetraethylammonium hydroxide or tetraethylammonium bromide.

[0011] The molar ratio of tetraethylammonium to silicon dioxide in the precursor is TEA / SiO 2 It is preferably 0.20 to 0.45. wherein TEA represents tetraethylammonium.

[0012] The aqueous solution of tetraethylammonium ions may contain fluoride as a mineralizer, and the molar ratio of fluoride to silicon dioxide in the precursor molding is preferably - / SiO 2 It is 0 to 0.3.

[0013] The molar ratio of water to silicon dioxide in the precursor is preferably H 2 O / SiO 2 5 to 40.

[0014] The hydrothermal crystallization temperature is preferably 135 to 170°C.

[0015] The hydrothermal crystallization time is preferably 48 to 120 hours.

[0016] The specific steps of treating Beta zeolite twice with acid, alkali and template are as follows:

[0017] Preparation of multi-level mesoporous Beta zeolite-based adsorbent: 3-6 g of hydrothermally obtained Beta zeolite is dissolved in 30-70 mL of deionized water, and then a 10 wt% citric acid solution is added thereto, stirred at room temperature for 1-3 h, centrifuged, washed with deionized water until neutral, dried at room temperature, and the acid-treated zeolite is added to 50-70 mL of a solution containing 0.3-0.6 g of NaOH and 2-3 g of hexadecyltrimethylammonium bromide (CTAB), maintained at 80-100° C. for 20-24 h, then filtered, washed with deionized water until neutral, dried at room temperature, and then calcined in a muffle furnace at 400-500° C. in a nitrogen atmosphere for 1-2 h to remove the template to obtain Beta zeolite a;

[0018] 3-6 g of the calcined Beta zeolite a is dissolved again in 30-70 mL of deionized water, and then a 10 wt% citric acid solution is added thereto, stirred at room temperature for 1 h, centrifuged, washed with deionized water until neutral, dried at room temperature, and the secondary acid-treated zeolite is added to 50-70 mL of a solution containing 0.3-0.6 g of NaOH and 2-3 g of hexadecyltrimethylammonium bromide (CTAB), kept at 80° C.-100° C. for 20-24 h, then filtered, washed with deionized water until neutral, dried at room temperature, and then calcined in a muffle furnace at 400-500° C. in a nitrogen atmosphere for 1-2 h to remove the template, thereby obtaining a hierarchical mesoporous Beta zeolite-based adsorbent;

[0019] Cu / hierarchical mesoporous Beta zeolite was prepared by impregnation method: a certain amount of copper acetate (C 4 H 6 CuO 4 ·H 2 O) is mixed with deionized water, placed in a constant temperature magnetic stirrer at 60-80°C and stirred for 10-30 minutes to dissolve, and an appropriate amount of the multi-stage mesoporous Beta zeolite prepared in step (2) is added under stirring, and after being stirred evenly, the mixture is transferred to a 100-120°C forced air drying oven for drying for 12-20 hours, and then transferred to a porcelain boat and cooled to room temperature, and then calcined in a muffle furnace at 450-500°C for 4-6 hours to obtain a zeolite-based catalytic adsorption material, wherein the Cu loading is 1-5wt% based on the total weight of the zeolite-based catalytic adsorption material.

[0020] The zeolite-based catalytic adsorption material is used for low-temperature catalytic oxidation of toluene. The toluene concentration is 1000-3000ppm and the reaction space velocity is 60000-96000mL·g -1 ·h -1 , the reaction temperature is 180-250℃.

[0021] The adsorption performance of the material was evaluated by a dynamic adsorption experiment. The reaction flow was controlled by a mass flow meter, and the adsorption temperature was controlled by a K-type thermocouple, heating tape, and a program temperature riser. 100 mg of the adsorbent was placed in a quartz reaction tube with an inner diameter of 8 mm. Quartz wool of a certain thickness was placed at both ends to prevent the material from entering the chromatogram with the air flow. The quartz tube was then placed in a reaction furnace. 2 Inject into the bubbling tank filled with toluene solution to obtain a certain concentration of gaseous toluene. Finally, gaseous toluene and N 2 The mixed gas was 100 mL min -1 The total flow rate of the adsorbent passes through the adsorbent. A gas chromatograph (Shanghai Fanwei GC-9860) equipped with a hydrogen flame ionization detector (FID) and a methane converter is used to detect the outlet toluene concentration. In the present invention, the adsorption amount of toluene by the adsorbent is calculated by the integral of the penetration curve, and the calculation formula is as follows:

[0022]

[0023] Where Q is the penetration adsorption capacity of toluene per unit mass of adsorbent (mg g -1 ), F is the total gas flow rate (mL min -1 ), M is the relative molecular weight of toluene, m is the mass of the adsorbent (g), C 0 and C are the initial concentration of toluene and the outlet concentration after passing through the adsorbent (ppm), respectively. s is the time corresponding to the adsorption breakthrough point (min).

[0024] The catalytic oxidation performance of the sample was characterized by the following method: 100 mg of the sample was placed in a quartz reaction tube with an inner diameter of 8 mm, the quartz reaction tube was placed in a reactor, and the raw material weight hourly space velocity was 60000 mL·g- 1 ·h -1 The outlet toluene concentration and CO were detected using a gas chromatograph (Shanghai Fanwei GC-9860) equipped with a hydrogen flame ionization detector (FID) and a methane reformer. 2 concentration. Toluene conversion and CO 2 The selectivity calculation formula is as follows:

[0025]

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. Beta zeolite seeds can be evenly distributed in the molding raw materials during the kneading process, and can serve as crystal nuclei to promote the amorphous silicon-aluminum species in the precursor to be converted into Beta zeolite under hydrothermal conditions and grow around the Beta zeolite seeds. Due to spatial limitations, staggered growth occurs, which can improve the strength of the generated integrated binder-free Beta zeolite, is beneficial to practical applications, and has achieved good technical results.

[0028] 2. Acid is used to destroy the O-Al bond on the surface of Beta zeolite to partially dealuminate to form a certain amount of defects in the zeolite structure, followed by partial desiliconization in an alkaline environment containing the template agent CTAB. During this process, a regular mesoporous structure is formed at the defective position of the zeolite. After two cycles of acid, alkali, and template agent treatment, a multi-level mesoporous structure is formed on the surface of Beta zeolite, increasing the effective active surface of Beta zeolite and greatly enhancing its adsorption activity for toluene.

[0029] 3. The Cu loading is low, and the zeolite-based catalytic adsorption material can achieve complete catalytic oxidation degradation of toluene under low temperature conditions, with low cost and unexpectedly good effect. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] Preparation of Beta Zeolite:

[0033] Weigh white carbon black, Beta zeolite seed (SiO 2 / Al 2 O 3 The molar ratio is 45), sodium aluminate, silica sol, and sodium silicate are mixed and formed, and then calcined at 550°C in an air atmosphere for four hours to obtain a 10Na 2 O∶0.25Al 2 O 3 ∶100SiO 2 The forming precursor has a seed crystal weight content of 20%.

[0034] The precursor prepared above was mixed with tetraethylammonium bromide (TEABr) and NaF aqueous solution to obtain a mixture which was placed in a crystallization kettle and crystallized at 150°C for 96 hours; - / SiO 2 The molar ratio is 0.30, TEA / SiO 2 The molar ratio is 0.45, H 2 O / SiO 2 The molar ratio is 40. The solid material obtained after crystallization is washed with distilled water, dried, and calcined at 550° C. for 4 hours in an air atmosphere to obtain Beta zeolite.

[0035] Preparation of hierarchical mesoporous Beta zeolite:

[0036] 5g of hydrothermally obtained Beta zeolite was dissolved in 50mL of deionized water, and then a 10wt% citric acid solution was added thereto, and stirred at room temperature for 1h. The mass ratio of the citric acid solution to the Beta zeolite was 6:1. After centrifugation, washing with deionized water until neutral, and drying at room temperature, the acid-treated zeolite was added to 50mL of a solution containing 0.3g NaOH and 2.5g hexadecyltrimethylammonium bromide (CTAB), and kept at 80°C for 24h. Then filter, wash with deionized water until neutral, and dry at room temperature. Then calcine at 450°C in a muffle furnace in a nitrogen atmosphere for 1h to remove the template to obtain Beta zeolite a.

[0037] 5g of calcined Beta zeolite a was dissolved again in 50mL of deionized water, and then 10wt% citric acid solution was added thereto and stirred at room temperature for 1h. The mass ratio of citric acid solution to Beta zeolite a was 6:1. After centrifugation, washing with deionized water until neutral, and drying at room temperature, the secondary acid-treated zeolite was added to 50mL of a solution containing 0.3g NaOH and 2.5g hexadecyltrimethylammonium bromide (CTAB) and kept at 80°C for 24h. Then filter, wash with deionized water until neutral, and dry at room temperature. Then calcine at 450°C in a muffle furnace in a nitrogen atmosphere for 1h to remove the template to obtain a multi-level mesoporous Beta zeolite.

[0038] Preparation of zeolite-based catalytic adsorption material: a certain amount of copper acetate (C 4 H 6 CuO 4 ·H 2 O) was mixed with deionized water, placed in a 60°C constant temperature magnetic stirrer and stirred for 10 minutes to dissolve, 1 g of multi-stage mesoporous Beta zeolite was added under stirring, and after stirring evenly, it was transferred to a 105°C forced air drying oven for drying for 12 hours, then transferred to a porcelain boat and cooled to room temperature, and then calcined in a 450°C muffle furnace for 4 hours. The Cu loading was 3 wt% based on the total weight of the catalytic adsorption material.

[0039] Comparative Example 1

[0040] Weigh white carbon black, Beta zeolite seed (SiO 2 / Al 2 O 3 The molar ratio is 45), sodium aluminate, silica sol, and sodium silicate are mixed and formed, and then calcined at 550°C in an air atmosphere for four hours to obtain a 10Na 2 O∶0.25Al 2 O 3 ∶100SiO 2 The forming precursor has a seed crystal weight content of 20%.

[0041] The precursor prepared above was mixed with tetraethylammonium bromide (TEABr) and NaF aqueous solution to obtain a mixture which was placed in a crystallization kettle and crystallized at 150°C for 96 hours; - / SiO 2 The molar ratio is 0.30, TEA / SiO 2 The molar ratio is 0.45, H 2 O / SiO 2 The molar ratio is 40. The solid material obtained after crystallization is washed with distilled water, dried, and calcined at 550° C. for 4 hours in an air atmosphere to obtain Beta zeolite.

[0042] Example 2

[0043] The adsorption performance of the material was evaluated by a dynamic adsorption experiment. The reaction flow was controlled by a mass flow meter, and the adsorption temperature was controlled by a K-type thermocouple, heating tape, and a program temperature riser. 100 mg of the adsorbent was placed in a quartz reaction tube with an inner diameter of 8 mm. Quartz wool of a certain thickness was placed at both ends to prevent the material from entering the chromatogram with the air flow. The quartz tube was then placed in a reaction furnace. 2 Inject into the bubbling tank filled with toluene solution to obtain a certain concentration of gaseous toluene. Finally, gaseous toluene and N 2 The mixed gas was 100 mL min -1 The total flow rate of passed through the adsorbent. The outlet toluene concentration was detected by a gas chromatograph (Shanghai Fanwei GC-9860) equipped with a hydrogen flame ionization detector (FID) and a methane reformer. The relevant adsorption effect is shown in Table 1 below.

[0044] Table 1: Penetration time and adsorption capacity of toluene for samples of Examples and Comparative Examples

[0045]

[0046] As can be seen from Table 1, compared with Beta zeolite that has not been post-treated with acid, alkali and CTAB, the Beta zeolite a treated once has a greatly improved penetration time for toluene, and the adsorption capacity has also been improved, indicating that the formation of a regular mesoporous structure formed by dealumination, desiliconization and self-assembly at the defective positions of the zeolite has greatly increased the effective active surface of the Beta zeolite and enhanced the adsorption performance of the Beta zeolite for toluene. After being treated with acid, alkali and CTAB again, its penetration time and adsorption capacity for toluene have been further improved, which can be attributed to the dealumination of the surface of the Beta zeolite, the dissolution of some structures in the desiliconization process, and the self-assembly to form a new regular mesoporous structure, thereby improving the adsorption performance of the Beta zeolite for toluene. Compared with the untreated Beta zeolite, its adsorption performance for toluene has been unexpectedly improved.

[0047] Example 3

[0048] The zeolite-based catalytic adsorption material prepared in Example 1 was used for low-temperature catalytic oxidation of toluene. The toluene concentration was 1000 ppm and the reaction space velocity was 60000 mL·g -1 ·h -1 When the reaction temperature rises to 180°C, the toluene conversion rate reaches 100%, and the CO 2 The selectivity reaches 100%, that is, when the loading amount of the metal Cu active component is maintained at a low level, complete catalytic oxidation degradation of toluene can be achieved at a low temperature of 180° C., which fully demonstrates the excellent activity of the catalytic adsorption material prepared by the present invention.

[0049] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for treating organic pollutants using a zeolite-based catalytic adsorption material, characterized in that: The zeolite-based catalytic adsorption material is used for low-temperature catalytic oxidation of toluene. The toluene concentration is 1000-3000ppm and the reaction space velocity is 60000-96000mL·g -1 ·h -1 , the reaction temperature is 180-250℃, The method for preparing the zeolite-based catalytic adsorption material comprises the following steps: (1) Preparation of Beta zeolite: A precursor containing a sodium source, a silicon source and an aluminum source is hydrothermally crystallized in a tetraethylammonium ion aqueous solution to convert it into Beta zeolite, wherein the sodium source Na2O is calculated as , the silicon source is calculated as SiO2, the aluminum source Al2O3 is calculated as , and the molar ratio of Na2O:Al2O3:SiO2 is X:Y:100, wherein X=2-40, Y=0.25-10; (2) Preparation of multi-level mesoporous Beta zeolite-based adsorbent: 3-6 g of hydrothermally obtained Beta zeolite was dissolved in 30-70 mL of deionized water, and then a 10 wt% citric acid solution was added thereto, stirred at room temperature for 1-3 h, centrifuged, washed with deionized water until neutral, dried at room temperature, and the acid-treated zeolite was added to 50-70 mL of a solution containing 0.3-0.6 g of NaOH and 2-3 g of hexadecyltrimethylammonium bromide (CTAB), kept at 80-100° C. for 20-24 h, then filtered, washed with deionized water until neutral, dried at room temperature, and then calcined in a muffle furnace at 400-500° C. in a nitrogen atmosphere for 1-2 h to remove the template to obtain Beta zeolite a; 3-6 g of the calcined Beta zeolite a is dissolved again in 30-70 mL of deionized water, and then a 10 wt% citric acid solution is added thereto, stirred at room temperature for 1 h, centrifuged, washed with deionized water until neutral, dried at room temperature, and the secondary acid-treated zeolite is added to 50-70 mL of a solution containing 0.3-0.6 g of NaOH and 2-3 g of hexadecyltrimethylammonium bromide (CTAB), kept at 80° C.-100° C. for 20-24 h, then filtered, washed with deionized water until neutral, dried at room temperature, and then calcined in a muffle furnace at 400-500° C. in a nitrogen atmosphere for 1-2 h to remove the template, thereby obtaining a hierarchical mesoporous Beta zeolite-based adsorbent; (3) Preparation of Cu / multi-level mesoporous Beta zeolite by impregnation method: a certain amount of copper acetate (C4H6CuO4·H2O) is mixed with deionized water, placed in a constant temperature magnetic stirrer at 60-80°C and stirred for 10-30 min to dissolve it, and an appropriate amount of the multi-level mesoporous Beta zeolite prepared in step (2) is added under stirring, and after stirring evenly, the mixture is transferred to a 100-120°C forced air drying oven for drying for 12-20 h, and then transferred to a porcelain boat and cooled to room temperature, and then calcined in a muffle furnace at 450-500°C for 4-6 h to obtain a zeolite-based catalytic adsorption material, wherein the Cu loading is 1-5 wt% based on the total weight of the zeolite-based catalytic adsorption material.

2. The method for treating organic pollutants according to claim 1, characterized in that: The silicon source includes at least one of silicon oxide, silica sol and silicate; the aluminum source includes at least one of aluminum oxide, aluminum salt and aluminate.

3. The method for treating organic pollutants according to claim 2, characterized in that: The silicon source or the aluminum source further includes Beta zeolite seeds.

4. The method for treating organic pollutants according to claim 3, characterized in that: The weight percentage of the Beta zeolite seed crystals in the precursor molded product is less than 80%.

5. The method for treating organic pollutants according to claim 1, characterized in that: Tetraethylammonium is derived from at least one of tetraethylammonium hydroxide or tetraethylammonium bromide; the molar ratio of tetraethylammonium to silicon dioxide in the precursor molded product, TEA / SiO2, is 0.20 to 0.45, wherein TEA represents tetraethylammonium.

6. The method for treating organic pollutants according to claim 5, characterized in that: The aqueous solution of tetraethylammonium ions contains fluoride as a mineralizer, and the molar ratio of fluoride to silicon dioxide in the precursor molding is F - / SiO2 is 0~0.

3.

7. The method for treating organic pollutants according to claim 1, characterized in that: The hydrothermal crystallization temperature is 135 to 170° C., and the hydrothermal crystallization time is 48 to 120 hours.

8. The method for treating organic pollutants according to claim 1, characterized in that: In step (2), the mass ratio of the citric acid solution to Beta zeolite and / or to Beta zeolite a is 4-8:

1.

9. The method for treating organic pollutants according to claim 1, characterized in that: In step (3), the mixture was placed in a 60°C constant temperature magnetic stirrer and stirred for 10 min.

10. The method for treating organic pollutants according to claim 1, characterized in that: In step (3), the drying temperature is 105° C., the drying time is 12 h, the roasting temperature is 250° C., and the roasting time is 4 h.